Pembelajaran Integral Tak Tentu Menggunakan Articulate Storyline di MA Miftahussalam - Shofiyana Noor Wijayanti; Adhina Rizkillah Harahap; Arum Qurrotulaini Pradjna Paramita; Sunarsih Sunarsih; Heru Tjahjana (Universitas Muhammadiyah Semarang, 2025)
Mathematics is often considered a difficult subject and is of little interest to students, which results in students having difficulty learning independently outside of school. The difficulty of class XI students in understanding mathematics material is the background for the need to use new technology, namely articulate storylines, so that mathematics learning is more innovative and interactive. This community service activity is divided into 2 stages, namely the preparation stage and the implementation stage. In the preparation stage, the community service team conducted interviews with class XI mathematics teachers at MA Miftahussaam to find out what material was still difficult for students to understand. The second stage of this community service activity is the implementation stage which includes a pre-test, providing learning companion modules, playing the Articulate Storyline video, and post-test. The results of community service regarding the use of Articulate Storyline media at MA Miftahussalam show that the average pre-test score of 25 students is 42.2. This average value shows that the level of students' understanding ability and interest in learning about Indefinite Integral material is still below the average standard, namely less than 50. Meanwhile, the average post-test score of 25 students is 72.2. This average value shows that the level of students' understanding ability and interest in learning about Integral Uncertain material has reached the standard value, namely more than 70. Meanwhile, if calculated using percentages, the percentage increase in value from pre-test to post-test is 71.09%. This percentage level can be stated to be quite good.